2023
DOI: 10.1021/acs.nanolett.3c00187
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of Amyloid-β Protofibrils and Actions of Anti-Amyloid-β Antibodies as Observed by High-Speed Atomic Force Microscopy

Abstract: Amyloid-β (Aβ) aggregation intermediates, including oligomers and protofibrils (PFs), have attracted attention as neurotoxic aggregates in Alzheimer's disease. However, due to the complexity of the aggregation pathway, the structural dynamics of aggregation intermediates and how drugs act on them have not been clarified. Here we used highspeed atomic force microscopy to observe the structural dynamics of Aβ42 PF at the single-molecule level and the effect of lecanemab, an anti-Aβ PF antibody with the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…We found that Lecanemab remained stable in binding to protofibrils and to globular oligomers, inhibiting the formation of large aggregates. These results provide direct evidence for a mechanism by which antibody drugs interfere with the Aβ aggregation process [ 109 ]. Another major hallmark of AD is abnormally phosphorylated tau protein.…”
Section: Discussionmentioning
confidence: 92%
“…We found that Lecanemab remained stable in binding to protofibrils and to globular oligomers, inhibiting the formation of large aggregates. These results provide direct evidence for a mechanism by which antibody drugs interfere with the Aβ aggregation process [ 109 ]. Another major hallmark of AD is abnormally phosphorylated tau protein.…”
Section: Discussionmentioning
confidence: 92%
“…The AFM technique was used to visualize the immobilization of the CCT complex on the surface coated with anti-PA tag antibody, which was covalently immobilized on mica, following the procedure described in the literature [54,55]. Briefly, 2 µL of 0.01% APTES (Sigma Aldrich, Burlington, MA, USA) diluted in ultra-pure water was applied to mica and incubated for 3 min, followed by two rounds of washing with ultra-pure water to remove any unbound APTES.…”
Section: Afm Analysismentioning
confidence: 99%
“…Uniquely designed as a bispecific antibody, LCN also enhances blood-brain barrier (BBB) permeability by recognizing the transferrin receptor 14 . Extensive research has shown that LCN possesses a strong affinity for oligomeric Aβ42 15 . It is distinguished by its dual ability to reduce brain Aβ42 protofibrils and inhibit the proliferation of Aβ42 fibrils 16 , showcasing superior clinical symptom improvement compared to Adu 11,17 .…”
Section: Introductionmentioning
confidence: 99%